2017
DOI: 10.1002/aqc.2778
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term habitat loss in a lightly‐disturbed population of the Indo‐Pacific humpback dolphin, Sousa chinensis

Abstract: Coastal and estuarine waters are important ecosystems with high primary and secondary productivity, but they are prone to the impacts of habitat loss caused by anthropogenic activities. For species exclusively inhabiting coastal and estuarine waters, such as the Indo‐Pacific humpback dolphin, Sousa chinensis, irreversible habitat loss can have dramatic implications for population viability. A Landsat image database was used to determine the extent of coastal changes along the northern Beibu Gulf, where a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 70 publications
(176 reference statements)
1
64
1
Order By: Relevance
“…Recent studies indicated the Dafengjiang River Estuary is one of the core habitats for humpback dolphins in the northern Beibu Gulf (Chen et al, ; Huang et al, ; Wu et al, ). The movement analysis based on LIR values presented a fluid habitat‐use dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated the Dafengjiang River Estuary is one of the core habitats for humpback dolphins in the northern Beibu Gulf (Chen et al, ; Huang et al, ; Wu et al, ). The movement analysis based on LIR values presented a fluid habitat‐use dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the Dafengjiang River Estuary, the Hepu Dugon Reserve is another core humpback dolphin habitat in the northern Beibu Gulf (Chen et al, ; Huang et al, ; Wu et al, ). Recent studies report different results between distribution gradients (Huang et al, ; Wu et al, ) and interhabitat communications (Chen et al, ). A cross‐matching of photo‐ID databases between the Dafengjiang River Estuary and Hepu Dugong Reserve study areas (Chen et al, ; Wang et al, ) and genetic comparison based on stranded carcasses (Alves et al, ; Parra et al, ), would help to clarify the above inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being highly subject to human‐derived disturbances, i.e. heavy shipping (Jefferson, ; Ross, Dungan, Hung, & Jefferson, ), pollution from rivers (Gui et al, ; Ross et al, ; Yeung et al, ), noise pollution (Ross et al, ; Wang et al, ), and habitat loss (Wu et al, ), estuaries have been identified as its preferred habitat (Jefferson, ; Jefferson & Hung, ; Wang et al, ). It is an interesting and important issue for species conservation to know why IPHDs favour an environment so affected by human activities.…”
Section: Introductionmentioning
confidence: 99%
“…; Wu et al . ). For the Bryde's whale in the northern Beibu Gulf, this study aimed to identify sites of occurrence of Bryde's whales based on citizen science information from collaborative fishermen, LEK information from questionnaire interviews and records from authors’ opportunistic surveys to provide preliminary knowledge of the Bryde's whale in the waters around Weizhou and Xieyang Islands before conducting systematically designed field surveys.…”
mentioning
confidence: 97%
“…To develop these baselines, however, field surveys generally need to be conducted for several years (as in Chen et al 2010Chen et al , 2016Jutapruet et al 2015;Xu et al 2015;Wang et al 2017;Wu et al 2017a). Local ecological knowledge (LEK) based on questionnaire surveys can provide qualitative, and sometimes quantitative, information on occurrence and distribution gradients of charismatic animals (Turvey et al 2010(Turvey et al , 2013Logan et al 2015;Wu et al 2017b). For the Bryde's whale in the northern Beibu Gulf, this study aimed to identify sites of occurrence of Bryde's whales based on citizen science information from collaborative fishermen, LEK information from questionnaire interviews and records from authors' opportunistic surveys to provide preliminary knowledge of the Bryde's whale in the waters around Weizhou and Xieyang Islands before conducting systematically designed field surveys.…”
mentioning
confidence: 99%